Analysis of Factors Influencing The Drop Out of Family Planning Acceptors - Widyastuti, Yuni; Menap, Menap; Sastrawan, Sastrawan; Pratiwi, Intan Gumilang (poltekkes kemenkes mataram, 2024)
Population issues are still the main focus of both developed and developing countries including Indonesia. The government through the Population and Family Planning Sector continues to strive to reduce the Total fertility Rate by reducing the drop out rate of contraceptive use. Drop out is the non-participation of fertile age couples to become family planning acceptors. The purpose of this study was to determine the factors that influence the drop out of family planning acceptors in West Lombok Regency. Previous studies stated that the factors causing drop out were knowledge, attitudes and distance from health services. The difference between this study and previous researchers is the research method used, the location of the study and the time of the study, and to determine the most dominant factors causing drop out. The research design used Cross-Sectional, a population of 135,076 with a sample size of 100 fertility age couple obtained randomly using the proportional to size method, the research instrument used a questionnaire. Data analysis used the chi square test to determine the effect and the multivariate logistic regression test to see the most dominant effect. Results: Chi Square test of knowledge factor obtained p value 0.000 < from alpha (0.05), motivation factor obtained p value 0.0005 < from alpha (0.05), access factor obtained p value 0.961 > from alpha (0.05), insurance ownership obtained p value 0.001 < from alpha (0.05) and work obtained p value 0.000 < from alpha (0.05) Conclusion: there is an influence of knowledge, motivation, insurance ownership and respondent's work with the occurrence of drop out in family planning acceptors while respondent access has no influence on the occurrence of drop out in West Lombok Regency. While the most dominant factor is motivation with OR value 5.575, meaning KB acceptors who do not have strong motivation have a risk or tendency of 5 to 6 times dropping out as family planning acceptors.